Analysing academics' entrepreneurial opportunities: The influence of academic self-efficacy and networks - Ignacio Mira-Solves; Marina Estrada de la Cruz; José María Gómez-Gras (European Research on Management and Business Economics (ERMBE), 2021)
Academic entrepreneurial opportunities are a key factor in the development of new spin-offs. This study examines the relationship between academic entrepreneurial opportunities perceived by academics and these academics' entrepreneurial self-efficacy (ESE) to determine which dimensions of ESE (among management, innovation, marketing, risk-taking and financial control) are significantly related to these opportunities. It also analyses how industrial and entrepreneurial networks, as part of the university's entrepreneurial ecosystem, influence this relationship. A quantitative method is used to achieve this goal, developing a structural equations model and applying partial least squares technique to analyse a sample of 388 Spanish academics. The results show that the dimensions of ESE related to variables such as management, innovation and marketing have a positive and significant relationship to perception of entrepreneurial opportunities. This situation is different, however, for dimensions such as risk-taking and financial control. Moreover, the findings show that entrepreneurial and industrial networks have a significant effect on this relationship.
Keywords: M13; 650; Academic entrepreneurial opportunities; Social networks; Industrial networks; Spin-offs; Entrepreneurial ecosystems